DAMPAK PENGEMBANGAN KAPAS TRANSGENIK TERHADAP PEREKONOMIAN WILAYAH DI KABUPATEN TAKALAR, BANTAENG, DAN BULUKUMBA - Irsyadi Siradjuddin (Jurnal Agroteknologi, 2011)
This research aim to know : (1) Technological adoption level (technological exploiting physical structure) cotton farmers, and (2) elegibility financial and earnings of cotton commodity in Regency of Takalar, Bantaeng, and Bulukumba. Result of this research indicate that: (1) Analysis mount the technological adoption of cotton transgenik in regency of Takalar, Bantaeng, and Bulukumba show the level adopt all production is high, except insektisida; and (2) Analyse elegibility financial is analyse the balance of acceptance and expense indicate that the cotton transgenik in all regency have the value B/C ratio and R/C ratio are highest, followed by maize and cotton non-transgenik. Analyse the break even point produce and price indicate that the cotton transgenik in all regency have the break even point produce and price lower followed by maize and cotton non-transgenik. Analyse of sensitives with the assumption of increase of price seed 50% indicating that cotton transgenik have the value B/C ratio is highest, followed by maize and cotton non-transgenik. Analysis of concerning farmer earnings indicate that the cotton transgenik give the better earnings compared by maize and cotton non-transgenic.